The genomic origin of the unique chaetognath body plan - Laura Piovani; Daria Gavriouchkina; Elise Parey; Luke A. Sarre; Katja T. C. A. Peijnenburg; José María Martín-Durán; Daniel S. Rokhsar; Noriyuki Satoh; Alex de Mendoza; Taichiro Goto; Ferdinand Marlétaz (Nature, 2025)
Abstract The emergence of animal phyla, each with their unique body plan, was a rapid event in the history of animal life, yet its genomic underpinnings are still poorly understood1. Here we investigate at the genomic, regulatory and cellular levels, the origin of one of the most distinctive animal phyla, the chaetognaths, whose organismal characteristics have historically complicated their phylogenetic placement2,3. We show that these characteristics are reflected at the cell-type level by the expression of genes that originated in the chaetognath lineage, contributing to adaptation to planktonic life at the sensory and structural levels4. Similarly to other members of gnathiferans (which also include rotifers and several other microscopic phyla)5,6, chaetognaths have undergone accelerated genomic evolution with gene loss and chromosomal fusions7,8. Furthermore, they secondarily duplicated thousands of genes9,10, without evidence for a whole-genome duplication, yielding, for instance, tandemly expanded Hox genes, as well as many phylum-specific genes. We also detected repeat-rich highly methylated neocentromeres and a simplified DNA methylation toolkit that is involved in mobile element repression rather than transcriptional control. Consistent with fossil evidence11,12, our observations suggest that chaetognaths emerged after a phase of morphological simplification through a reinvention of organ systems paralleled by massive genomic reorganization, explaining the uniqueness of their body plan.